Understanding flavour perception of espresso coffee by the combination of a dynamic sensory method and in-vivo nosespace analysis. (March 2015) - Charles, Mathilde; Romano, Andrea; Yener, Sine; Barnabà, Massimo; Navarini, Luciano; Märk, Tilmann D.; Biasoli, Franco; Gasperi, Flavia
Abstract: The first goal of this work was to gain insight into the mechanism underlying flavour perception and aroma release by coupling two real-time methods: Temporal Dominance of Sensations (TDS) and nosespace (NS) analysis via Proton Transfer Reaction–Time of Flight–Mass Spectrometry (PTR–ToF–MS). The second goal was to investigate the impact of roasting degree and sugar addition on aroma release and perception in espresso coffee. A set of four coffee samples, two roasting degrees and two sugar levels, has been used for both sensory and instrumental measurements. The in-mouth flavour evolution in terms of dominant sensations was measured by mean of TDS carried out by 18 trained judges with a 9-attribute list ( Sweet, Sour, Bitter, Astringent, Roasted, Burnt, Caramel, Nutty and Vegetal ). The same judges were subjected simultaneously to NS analysis in order to identify and quantify the volatile compounds reaching their olfactory receptors during coffee consumption. A significant effect of roasting was observed with both techniques. More compounds and in larger quantity were released when increasing roasting degree, which was described sensorially as a greater dominance of the attributes Burnt, Roasted, Astringent and Bitter . Sugar addition did not significantly affect the aroma release of volatile compounds as demonstrated by the NS profiles of judges while changing completely the way the coffee was sensorially perceived in mouth. As expected, sweet taste became dominant over bitter and sour but it increased more globally the flavour complexity with Caramel and Nutty notes reducing the Roasted or Burnt ones. This result emphasises the presence of taste–smell perceptual interactions, due to congruence effect between sweet taste and some flavours of coffee, and the potentialities of this combination of dynamic methods to study them. Besides, the treatment of NS data using clustering methods revealed two different release behaviours, which permitted to identify potential TDS markers. Highlights: Pairing dynamic sensory and instrumental methods seem relevant for flavour studies. Roasting was a factor of sample discrimination both sensorially and instrumentally. The sugar addition modifies sensory perception of coffee but not its aroma release. Sensory interactions were pointed out with the coupling of the two dynamic methods. Possible "Temporal Dominance Markers" were identified with nosespace measurements.